2021
DOI: 10.1136/annrheumdis-2021-220512
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two dose escalation strategies of methotrexate in active rheumatoid arthritis: a multicentre, parallel group, randomised controlled trial

Abstract: ObjectivesThere are no head-to-head trials of different dose escalation strategies of methotrexate (MTX) in RA. We compared the efficacy, safety and tolerability of ‘usual’ (5 mg every 4 weeks) versus ‘fast’ (5 mg every 2 weeks) escalation of oral MTX.MethodsThis multicentre, open-label (assessor blinded) RCT included patients 18-55 years of age having active RA with disease duration <5 years, and not on DMARDs. Patients were randomized 1:1 into usual or fast escalation groups, both groups starting MTX at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Another Indian investigator-blinded trial (high RoB) compared two different MTX dosage escalation strategies in MTX-naïve patients—starting with 15 mg once weekly, MTX was either increased by 5 mg every 2 weeks or by 5 mg every 4 weeks. No efficacy differences in EULAR good response rates were observed at week 16 (22.5% vs 28.1%; p=0.39; for every 2 weeks and every 4 weeks MTX escalation, respectively) 12…”
Section: Resultsmentioning
confidence: 83%
“…Another Indian investigator-blinded trial (high RoB) compared two different MTX dosage escalation strategies in MTX-naïve patients—starting with 15 mg once weekly, MTX was either increased by 5 mg every 2 weeks or by 5 mg every 4 weeks. No efficacy differences in EULAR good response rates were observed at week 16 (22.5% vs 28.1%; p=0.39; for every 2 weeks and every 4 weeks MTX escalation, respectively) 12…”
Section: Resultsmentioning
confidence: 83%
“…The DAS28-CRP is widely used as an indicator of RA disease activity and response to treatment, and clinical trials have used DAS28 to assess treatment effect ( Gardiner et al, 2005 ; Jain et al, 2021 ; Zhang et al, 2022 ). A change of ≥1.2 score is considered clinically significant difference ( Van Gestel et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies were conducted in Europe ( n = 5, 41.7%), followed by Asia ( n = 4, 33.3%) and America ( n = 3, 25.0%). The included studies were undertaken in a single centre (including hospitals or clinics), while 4 trials were multicenter studies [ 31 , 34 – 36 ]. Included studies were grouped into two broad categories that represent (i) the different starting dosages and the plan for dose escalation ( n = 9) [ 28 , 29 , 33 – 41 ] and (ii) the routes of administration for MTX ( n = 3) [ 30 – 32 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included trials recruited patients with a broad range of time from RA diagnosis (from 2.1 to 14.4 years), with a mean of 5.8 (± 4.8) years. Only two studies [ 28 , 36 ] reported data on body mass index, with a mean of 24.2 (± 0.9) kg/m 2 . The mean Disease Activity Score for 28 joints (DAS28) score was reported by three trials [ 36 , 38 , 39 ] with scores ranging from 4.5 to 5.4 (mean 5.2 [± 0.4]), while only one study [ 40 ] provided data on the basal ACR functional class with a mean of 1.2 (± 1.3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation